Soldiers and protest: a set-theory perspective on military repression of anti-regime mass mobilization in autocracies - Eschenauer-Engler, Tanja (International interactions, 2023)
This article studies the military’s decision to repress major, regime-threatening mass protests in autocracies or refuse violence from a set-theoretic perspective. So far, knowledge on such diametrical military reactions has been mainly derived from temporally and geographically restricted small-N analyses. This article expands on existing research by studying the combined relevance of five factors in a Qualitative Comparative Analysis. This configurational method identifies which factors or combinations thereof induce an outcome and assumes that the same phenomenon can be reached through different causal pathways. Using a sample of 24 nonviolent anti-regime uprisings in autocracies between 1986 and 2011, the analysis uncovers that no factor is individually sufficient for military repression. Instead, military repression arises from an interplay of factors and different combinations lead to repression: Militaries repress when (1) they are materially spoiled and internally cohesive, or (2) enjoy financial benefits, are recruited along sectarian lines, and there is conscription. They refuse repression if (1) they are incohesive and not recruited along social cleavages, or (2) are not materially spoiled. Finally, the analysis shows that different ensembles of determinants are at work in different socio-political environments. The article’s findings could inspire ideas for future research in the broader field of civil–military relations. Acknowledging the complexity of military behavior could deliver precious insights into the determinants of armed forces’ conduct in other highly relevant areas, such as coups or armed conflicts.